Dificultades de los estudiantes Húngaros en el aprendizaje del español - Ábrahám, Szilvia (Acta Hispanica, 2008)
The aim of the paper is to examine, with the methodology of contrastive analysis, the difficulties Hungarian students face in the process of learning Spanish, both in the fields of oral and written assignments. Thus, the paper examines the problematics of teaching both grammar (nouns, verbs, tenses and modes) and pronunciation. Although not all linguists agree on the merits of the use of the contrastive method, it is still indispensable. This method makes it possible to examine the impact of the connection between the mother tongue, and the second and third acquired language, and explore similarities and differences between different languages. The paper applies the contrastive method and its principal focus to the process of teaching and learning Spanish. The author proposes that the use of this method makes it possible to identify and classify the most typical mistakes made by the native Hungarian student, thus making the learning process more easy and effective, and also contributing to the efficiency of the language teacher's work.